A study on the penicilin g, ampicilin and penicilin v residues in milk collected from some small dairy factories in konya - Ömer Demet; Ahmet Acet; Bünyamin Traş; A. Levent Baş; İsa Eğilmez (Eurasian Journal of Veterinary Sciences)
In this study, penicilin residues were studied in fifty milk samples collected from small dairy factories in Konya by HPLC. Penicilin G-potasyum was found in six of the milk samples analysed. The limit level of penicilin G determined in milk was 0.385,ug/kg the highest level was 12.032 ug/kg, the average level was calculated as 4 ug/kg. No penicilin V and ampicilin were found in any samples.